Cardiovascular risk among 6-8-year-old children living in urban and rural communities in Ecuador: A cross-sectional analysis - Vargas-Rosvik, Signe; Lazo-Verdugo, Nelly; Escandón, Samuel; Ochoa-Avilés, Cristina; Baldeón-Rojas, Lucy; Ochoa-Avilés, Angélica (Frontiers in Nutrition, 2022)
Cardiovascular diseases have their origins in childhood. At least 20% of children and adolescents in Latin America are overweight or obese. However, little is known regarding the cardiovascular risk of young children living in the region. This paper aims to identify associations between socio-demographics, adiposity, and dietary intake with cardiometabolic risk among children between 6- and 8-years old living in urban and rural Andean regions of Ecuador. A cross-sectional study was conducted among 267 children attending elementary schools between February and August 2018. Sociodemographic data were collected using a structured interview. Bodyweight, height, and waist circumference were measured in duplicate; blood samples were taken after overnight fasting to determine blood lipids, hepatic enzymes, and adipokines; food intake data was assessed by two 24-hour recalls administered to the guardians. Associations between cardiometabolic risk (i.e., blood lipids, hepatic enzymes, and adipokines) with sociodemographic characteristics, dietary intake, and waist circumference were tested using multiple hierarchical regression models. Twenty-nine percent of the children were overweight or obese, 12% had low HDL levels, and over 18% had high levels of LDL and triglycerides. Children living in the urban region had lower levels of HDL (β -4,07 mg/dL; 95% CI: -7,00; -1,15; P =0,007) but higher levels of LDL cholesterol (β 8,52 mg/dL; 95% CI: 1,38;15,66; P= 0,019). Hepatic enzymes were also higher among urban children (SGOT: β% 22,13; 95% CI: 17,33;26,93; P<0,001. SGPT: β 0,84 U/L; 95% CI: 0,09;1,59; P =0,028). Leptin blood levels were higher (β% 29,27; 95% CI: 3,57;54,97; P =0,026), meanwhile adiponectin plasma concentrations were lower among urban children (β% -103,24; 95% CI: -58,9; -147,58; P =<0,001). Fiber intake was inversely associated with total cholesterol (β -9,27 mg/dL; 95% CI –18,09;-0,45; P =0,040) and LDL cholesterol blood levels (β -9,99 mg/dL; 95% CI: -18,22;-1,75; P =0,018). Our findings demonstrate that young children are at high cardiovascular risk; if no actions are taken, the burden of non-communicable diseases will be substantial. The differences in risk between rural and urban areas are evident; urbanization might predispose children to a different reality and, in most cases, result in poor habits.